Mechanism of IRSp53 inhibition by 14-3-3 - David J. Kast (Nature Portfolio, 2019)
IRSp53 is a key regulator of filopodia formation and cell migration. Here, the authors elucidate a mechanism of phosphorylation-dependent inhibition of IRSp53 by 14-3-3, which impedes the interactions of IRSp53 with membranes and downstream cytoskeletal effectors.